Lithuanian Intra-Industry Trade with the Main Partner Countries - Rimkus, Vladas (Lithuanian Journal of Statistics, 2012)
The paper deals with the analysis of Lithuanian intra-industry trade. The largest foreign trade partner countriesselected for the analysis are as follows: Russia, Germany, Latvia, and Poland. An increase in the extent of intra-industry tradestimulates interest in this phenomenon. Traditional trade theories cannot explain why some countries trade in differentiatedproducts. Some economists think that intra-industry trade is based on monopolistic competition and economies of scale,which point that any countries located close to each other will trade with each other in similar products the more intensively,the more they are similar to each other with regard to both economic development and geographical resources. Variousindices are used to assess the intensiveness of intra-industry trade. Calculations provided in the paper are carried out applyingthe Grubel ˗ Lloyd index, which is the most frequently used for this purpose. The paper analyses changes in trade during theperiod of 2005 ˗ 2011 based on the data of Statistics Lithuania according to the Combined Nomenclature of goods. Theobject of research is trade between Lithuania and the above-mentioned countries. The methods of research are as follows:analysis of scientific literature and description, analysis of Lithuanian foreign trade statistics.
Keywords: export; import; intra - industry trade; Grubel ˗ Lloyd index